Regrowth after kelp harvesting in Nord-Trøndelag, Norway. (31st July 2016) - Steen, Henning; Moy, Frithjof E.; Bodvin, Torjan; Husa, Vivian
Abstract : In 2010, harvesting of kelp ( Laminaria hyperborea ) was performed for the first time in the county of Nord-Trøndelag, Norway. Underwater video surveys were performed just prior to harvesting and then on a yearly basis over a 4-year period to document the development of the kelp vegetation and sea urchin abundances. In addition, kelp plants were collected before harvesting and then again 4 years later for measurements of plant morphology, age, cortical growth and epiphytes. After 4 years, L. hyperborea had regained its dominance at the harvested sites, however, plant age, sizes and epiphytes were still below pre-harvesting levels. However, the kelp biomass appeared restored 4 years after harvesting, because of the high density of the recovering kelp vegetation. Furthermore, measurements of the cortical growth zones in transverse section of the stipes of the recovering kelp plants showed a higher growth rate during the post-harvesting period, than in plants from pristine kelp beds. Abundance of sea urchins was low during the entire monitoring period and grazing effects on the recovering kelp vegetation, at the harvested sites, appeared to be small. Interestingly, the age structure of plants collected 4 years after harvesting showed that kelp recruits present as understory vegetation prior to harvesting, must have contributed substantially to the restocking of kelp. However, the density of understory kelp recruits 4 years after harvesting was significantly lower than it had been prior to harvesting, and this may lead to a slower recovery if future harvests occur before the stocks of understory kelp recruits are restored.